External assessment and Mathematics teaching: impacts of Spaece on curriculum practices in Ceará, Brazil - Pereira, Océlio Fernandes; Olgin, Clarissa de Assis (Educação matemática debate, 2025)
The study investigated the impact of external assessments, focusing on the Permanent Basic Education Assessment System of Ceará. The objective was to analyze how these assessments influence curriculum practices and student performance, especially in Mathematics teaching. Using a qualitative approach, the study involved mapping ten academic works selected from the Capes database of theses and dissertations. The works analyzed address the use of educational technologies, pedagogical strategies, and the application of statistical models in external assessments. The results indicate that these assessments significantly affect curriculum organization and the methodologies adopted by teachers. The conclusion is that it is essential to use assessments in a balanced manner, prioritizing diagnosis and pedagogical intervention. The study investigated the impact of external assessments, focusing on the Permanent Basic Education Assessment System of Ceará. The objective was to analyze how these assessments influence curriculum practices and student performance, especially in Mathematics teaching. Using a qualitative approach, the study involved mapping ten academic works selected from the Capes database of theses and dissertations. The works analyzed address the use of educational technologies, pedagogical strategies, and the application of statistical models in external assessments. The results indicate that these assessments significantly affect curriculum organization and the methodologies adopted by teachers. The conclusion is that it is essential to use assessments in a balanced manner, prioritizing diagnosis and pedagogical intervention. El estudio investigó el impacto de las evaluaciones externas, centrándose en el Sistema de Evaluación Permanente de la Educación Básica de Ceará. El objetivo fue analizar cómo estas evaluaciones influyen en las prácticas curriculares y el rendimiento estudiantil, especialmente en la enseñanza de las Matemáticas. Con un enfoque cualitativo, el estudio incluyó el mapeo de diez producciones académicos seleccionadas de la base de datos de tesis y disertaciones de Capes. Las producciones analizadas abordan el uso de tecnologías educativas, estrategias pedagógicas y la aplicación de modelos estadísticos en las evaluaciones externas. Los resultados indican que estas evaluaciones afectan significativamente la organización curricular y las metodologías adoptadas por el profesorado. La conclusión es que es esencial utilizar las evaluaciones de forma equilibrada, priorizando el diagnóstico y la intervención pedagógica.